2018
DOI: 10.1111/cch.12604
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of trust beliefs in physicians by children with asthma and their mothers: Relations with children's adherence to medical regimes and quality of life

Abstract: The findings yield support for the conclusions that (a) trust beliefs in physicians by children with asthma promote their adherence and quality of life and (b) socialization of trust beliefs in physicians is a mutual mother-child process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This consideration leads to our fourth and final consideration. The FYI and Q-CHAT, as with many other questionnaires for early identification of autism, are affected by the quality of the relationships and trust towards the physicians [ 96 , 97 ], highlighting the importance of the parent-pediatrician relationship. If parents trust their pediatrician, they would likely be more willing to undergo evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…This consideration leads to our fourth and final consideration. The FYI and Q-CHAT, as with many other questionnaires for early identification of autism, are affected by the quality of the relationships and trust towards the physicians [ 96 , 97 ], highlighting the importance of the parent-pediatrician relationship. If parents trust their pediatrician, they would likely be more willing to undergo evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…69 Further, there appears to be reciprocal influence in attributions about health care providers, particularly trust or distrust in physicians, between parents and children. 70 Cohort effects in health literacy may stem from a range of factors, including experiences in both formal education and informal learning opportunities, social media, healthcare access, living environment, and health behaviors. 71…”
Section: Perceptions Of Self and Othersmentioning
confidence: 99%
“…Cultural and linguistic communication between HCPs and their patients plays a significant role in their health and has a profound effect on health outcomes (Patel et al, 2018;Rotenberg & Petrocchi, 2018). For example, one of the PI's previous studies demonstrated that CG perceptions related to the HCP's non-verbal communication influenced the return visit for the child (Dowell, 2015).…”
Section: Cultural and Linguistic Communication Of Healthcare Providermentioning
confidence: 99%